Biomechanical investigations on the total knee arthroplasty - Fonseca, F.
The main objective of this paper is to present the research work being performed on Total Knee Arthroplasty (TKA) using finite element analysis. Results obtained within numerical simulations evidence that the design of the type of knee prosthesis can be related to clinical findings like pain, bone atrophy and hypertrophy and fractures.